Antibacterial and wear-resistant ceramic coating based on micro-nano composite structure
Patent Information
- Application Number
- CN202610562725.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-27
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-04-27
AI Technical Summary
[0005]针对现有技术的不足,本发明提供了一种基于微纳复合结构的抗菌耐磨陶瓷涂料,解决了现有的陶瓷涂料普遍存在抗菌性能和耐磨性能差的问题
[0031](1)本发明技术方案中,在碳纤维表面合成片状纳米二硫化钼,一方面,合成的片状纳米二硫化钼具有较高的耐磨性能,能够消耗由摩擦产生的能量,提高陶瓷涂料的耐磨性,且碳纤维作为片状纳米二硫化钼的载体,能够负载较多的片状纳米二硫化钼,增强陶瓷涂料的耐磨性能,此外,碳纤维具有优异的长径比,复配片状纳米二硫化钼,能够杂乱分散在陶瓷涂料中,与陶瓷涂料基体形成机械互锁,提高碳纤维和片状纳米二硫化钼与陶瓷涂料的结合力。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of ceramic coating technology, and more specifically to an antibacterial and wear-resistant ceramic coating based on a micro-nano composite structure. Background Technology
[0002] Ceramic coatings are water-based inorganic coatings prepared using nano-inorganic compounds as film-forming substances and water as a solvent through sol-gel technology. They combine the flexibility of organic materials with the high-temperature resistance of inorganic materials. The coating can reach a hardness of 8-9H, with a long-term temperature resistance of 400-800℃ and a short-term maximum temperature resistance of 1200℃. Its components include polysiloxane compounds, acrylic resins, and quartz powder. After 5000 hours of weathering testing, the gloss retention rate exceeds 99%. It is resistant to acid and alkali immersion, freeze-thaw resistance, and is waterproof and wear-resistant. It also has a non-stick effect and a variety of color options, making it suitable for building interior and exterior walls, transportation vehicles, home appliances, and pipeline corrosion protection.
[0003] Existing ceramic coatings generally have poor antibacterial and wear-resistant properties, and cannot simultaneously meet the requirements of high wear resistance and antibacterial properties. The most common approach is to directly add various antibacterial agents such as silver and zinc oxide to the coating. However, these additive antibacterial agents may migrate and degrade in the coating, leading to a decrease in antibacterial properties and thus limiting their application. Furthermore, the coating is easily scratched and worn during frequent cleaning and use, which not only damages the appearance but may also cause the antibacterial function to be lost due to damage to the surface structure. Summary of the Invention
[0004] Technical problems to be solved
[0005] To address the shortcomings of existing technologies, this invention provides an antibacterial and wear-resistant ceramic coating based on a micro-nano composite structure, which solves the problem of poor antibacterial and wear-resistant properties that are common in existing ceramic coatings.
[0006] Technical solution
[0007] To achieve the above objectives, the present invention provides the following technical solution:
[0008] An antibacterial and wear-resistant ceramic coating based on a micro-nano composite structure comprises the following raw materials in parts by weight: 60-80 parts silica sol, 10-20 parts phenyltriethoxysilane, 0.5-1 part surfactant, 5-8 parts antibacterial and wear-resistant aggregate, 3-4 parts zeolite powder, 2-5 parts calcium carbonate powder, 3-6 parts quartz powder, 0.1-0.5 parts defoamer, 1-3 parts dispersant, 3-5 parts coupling agent, and 80-100 parts deionized water;
[0009] The antibacterial and wear-resistant aggregate is obtained by reacting modified carbon fiber and glucose together, and then reacting them with curcumin and tannic acid.
[0010] The modified carbon fiber is obtained by synthesizing sheet-like nano-molybdenum disulfide on the surface of carbon fiber, and then reacting it with zinc acetate and ammonia.
[0011] Furthermore, the antibacterial and wear-resistant aggregate is specifically prepared by the following steps:
[0012] A1. Mix carbon fiber, sodium dodecylbenzenesulfonate and deionized water, stir, add ammonium molybdate tetrahydrate and thiourea, stir evenly, place in a reaction vessel, perform hydrothermal treatment at 220-250℃ for 14-16h, cool to room temperature, take out the reactant, wash the reactant, dry it, and obtain carbon fiber loaded with sheet-like nano molybdenum disulfide.
[0013] A2. Add carbon fibers loaded with sheet-like nano molybdenum disulfide and gallic acid to deionized water, stir, add zinc acetate, stir evenly, add ammonia to adjust pH, stir, place in a reaction vessel, and hydrothermally react at 170-190℃ for 2-4 hours. Cool to room temperature, take out, wash, and dry to obtain modified carbon fibers.
[0014] A3. Mix glucose and ethanol, stir until completely dissolved, add modified carbon fiber, stir evenly, dry until ethanol evaporates, place in a tube furnace, add potassium hydroxide solution, purge with nitrogen, carbonize at 800-900℃ for 3-5 hours, cool to room temperature, remove, wash, and dry to obtain composite carbon fiber.
[0015] A4. Add composite carbon fiber, curcumin and tannic acid to acetone and stir evenly to obtain antibacterial and wear-resistant aggregate.
[0016] Furthermore, in the A1 reaction process described above, sodium dodecylbenzenesulfonate, as a surfactant, can coat the surface of carbon fibers, allowing the carbon fiber surface to carry sulfonate ions. After hydrothermal treatment, ammonium molybdate tetrahydrate decomposes and releases molybdenum ions, which can combine with the sulfonate ions carried on the carbon fiber surface. Thiourea decomposes at high temperature and releases sulfur elements, which can undergo a sulfidation reaction with molybdenum ions to form molybdenum disulfide crystal nuclei. After the reaction continues, the molybdenum disulfide crystal nuclei grow, thereby achieving the synthesis of sheet-like nano-molybdenum disulfide on the carbon fiber surface, resulting in carbon fibers loaded with sheet-like nano-molybdenum disulfide.
[0017] Furthermore, in the A2 reaction process described above, gallic acid dissolves in hot water and has good adhesive properties, enabling it to adhere to the surface of carbon fibers loaded with sheet-like molybdenum disulfide nanoparticles. This allows the phenolic hydroxyl groups carried by the carbon fibers to adsorb zinc ions from zinc acetate. After adjusting the reaction solution to alkalinity with ammonia, hydroxides are formed on the surface of the carbon fibers loaded with sheet-like molybdenum disulfide nanoparticles. After hydrothermal treatment, the hydroxides decompose upon heating to form nano-zinc oxide, thus achieving the synthesis of nano-zinc oxide on the surface of carbon fibers loaded with sheet-like molybdenum disulfide nanoparticles, resulting in modified carbon fibers.
[0018] Furthermore, in the A3 reaction process described above, glucose and ethanol form a glucose mixture, which is coated on the surface of the modified carbon fiber. After high-temperature carbonization, the glucose decomposes upon heating to form a dense carbon layer. Potassium hydroxide, as an activator, decomposes upon heating to form channels on the surface of the dense carbon layer, thereby achieving the formation of a porous carbon layer on the surface of the modified carbon fiber and obtaining composite carbon fiber.
[0019] Furthermore, during the A4 reaction process described above, the phenolic hydroxyl groups in tannic acid can bind with the hydroxyl groups in curcumin through hydrogen bonds, and the phenolic hydroxyl groups in tannic acid can also bind with the hydroxyl groups on the surface of the composite carbon fiber through hydrogen bonds, so that curcumin and tannic acid are coated on the surface of the composite carbon fiber, resulting in an antibacterial and wear-resistant filler.
[0020] Further, in step A1, the mass ratio of the carbon fiber, sodium dodecylbenzenesulfonate, deionized water, ammonium molybdate tetrahydrate, and thiourea is (1.5-2):(0.1-0.3):(80-100):(1.5-2):(1-2).
[0021] Further, in step A2, the mass ratio of the carbon fiber loaded with sheet-like molybdenum disulfide nanoparticles, gallic acid, deionized water, and zinc acetate is (1.5-2):(0.1-0.3):(80-120):(2-3).
[0022] Further, in step A3, the mass ratio of glucose, ethanol, modified carbon fiber and potassium hydroxide solution is (2-2.3):(40-50):(2.5-3):(1-1.5).
[0023] Further, in step A4, the mass ratio of the composite carbon fiber, curcumin, tannic acid, and acetone is (2-3):(1.2-1.5):(1-1.5):(50-60).
[0024] Furthermore, the surfactant is octadecyltrimethylammonium chloride, and the coupling agent is KH550.
[0025] Furthermore, the dispersant is selected from one of dispersant LD-64190 and dispersant LD-6408.
[0026] Furthermore, the defoamer is selected from BYK-024 defoamer and BYK-055 defoamer.
[0027] Furthermore, a method for preparing an antibacterial and wear-resistant ceramic coating based on a micro-nano composite structure includes the following steps:
[0028] S1. Mix silica sol, phenyltriethoxysilane and surfactant, stir at 40-50℃ for 2-4 hours, keep warm at 30-40℃ for 2-4 hours, and then mix with half of the deionized water in the formula to obtain nano-ceramic emulsion.
[0029] S2. Mix the nano-ceramic emulsion with zeolite powder, calcium carbonate powder, quartz powder, defoamer, antibacterial wear-resistant aggregate, dispersant, coupling agent and remaining deionized water, and stir at 300-500 r / min for 20-40 min to obtain antibacterial wear-resistant ceramic coating.
[0030] Beneficial technical effects
[0031] (1) In the technical solution of the present invention, sheet-like nano-molybdenum disulfide is synthesized on the surface of carbon fiber. On the one hand, the synthesized sheet-like nano-molybdenum disulfide has high wear resistance and can consume the energy generated by friction, thereby improving the wear resistance of ceramic coating. On the other hand, carbon fiber, as the carrier of sheet-like nano-molybdenum disulfide, can load more sheet-like nano-molybdenum disulfide, thereby enhancing the wear resistance of ceramic coating. Furthermore, carbon fiber has an excellent aspect ratio. When combined with sheet-like nano-molybdenum disulfide, it can be randomly dispersed in ceramic coating, forming a mechanical interlock with the ceramic coating matrix, thereby improving the bonding force between carbon fiber and sheet-like nano-molybdenum disulfide and ceramic coating.
[0032] (2) In the technical solution of the present invention, nano zinc oxide is synthesized on the surface of carbon fiber loaded with sheet-like nano molybdenum disulfide. On the one hand, the synthesized nano zinc oxide, as an inorganic antibacterial agent, can improve the antibacterial activity of ceramic coatings. On the other hand, the nano zinc oxide is filled between the sheet-like nano molybdenum disulfide. Under the action of the sheet-like nano molybdenum disulfide, the nano zinc oxide is prevented from easily migrating and precipitating during the process of frequent cleaning, scratching and abrasion of ceramic coatings, thus affecting the antibacterial activity of ceramic coatings.
[0033] (3) In the technical solution of the present invention, a porous carbon layer is formed on the surface of the modified carbon fiber. On the one hand, the synthesized porous carbon layer has high adsorption performance and can adsorb and fix the nano zinc oxide particles on the surface of the modified carbon fiber, preventing the nano zinc oxide from easily migrating and precipitating during the frequent cleaning, scratching and abrasion of the ceramic coating, thus affecting the antibacterial activity of the ceramic coating. On the other hand, when the ceramic coating comes into contact with bacteria, the adsorption performance of the porous carbon layer can enable the bacteria to enter the pores, increase the penetration time of the bacteria, and the bacteria inhaled into the pores are eliminated under the action of nano zinc oxide, thereby achieving the purpose of the porous carbon layer blocking and the nano zinc oxide sterilizing.
[0034] (4) In the technical solution of the present invention, the composite carbon fiber is chemically bonded to the oxygen-containing functional groups contained in curcumin and tannic acid. On the one hand, curcumin and tannic acid form an organic antibacterial layer on the surface of the composite carbon fiber and are added to the ceramic coating to form an organic-inorganic antibacterial system, thereby enhancing the antibacterial properties of the ceramic coating. On the other hand, curcumin and tannic acid provide a large number of oxygen-containing functional groups on the surface of the composite carbon fiber, thereby improving the dispersibility of the composite carbon fiber in the ceramic coating and enhancing the antibacterial and wear-resistant properties of the ceramic coating.
[0035] (5) In the technical solution of the present invention, silica sol, phenyltriethoxysilane and surfactant are mixed to form an inorganic nano-ceramic emulsion, which is then mixed with zeolite powder, calcium carbonate powder, quartz powder, defoamer, antibacterial wear-resistant aggregate, dispersant and coupling agent to form a micro-nano composite structure antibacterial wear-resistant ceramic coating. The micron-sized ceramic aggregate forms a graded reinforcement system with zeolite powder, calcium carbonate powder, quartz powder and antibacterial wear-resistant aggregate, which has high antibacterial activity and wear resistance. Detailed Implementation
[0036] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0037] The raw materials used in the embodiments of this invention are shown below, and all reagents used are analytical grade.
[0038] Silica sol, with a solid content of 30% and a particle size of 100nm, was purchased from Qingdao Ocean Chemical Co., Ltd.
[0039] The surfactant is octadecyltrimethylammonium chloride, the defoamer is BYK-024 defoamer, the dispersant is dispersant LD-64190, and the coupling agent is KH550.
[0040] Quartz powder (1250 mesh), purity ≥99.5%, Mohs hardness 7.0.
[0041] Zeolite powder (1250 mesh), clinoptilolite.
[0042] The carbon fiber has a diameter of 0.1 μm and a length of 5 μm.
[0043] Example 1
[0044] An antibacterial and wear-resistant ceramic coating based on a micro-nano composite structure comprises the following raw materials in parts by weight: 60 parts silica sol, 10 parts phenyltriethoxysilane, 0.5 parts octadecyltrimethylammonium chloride, 5 parts antibacterial and wear-resistant aggregate, 3 parts zeolite powder, 2 parts calcium carbonate powder, 3 parts quartz powder, 0.1 parts BYK-024 defoamer, 1 part dispersant LD-64190, 3 parts KH550, and 80 parts deionized water;
[0045] A method for preparing an antibacterial and wear-resistant ceramic coating based on a micro-nano composite structure includes the following steps:
[0046] S1. Mix silica sol, phenyltriethoxysilane and octadecyltrimethylammonium chloride, stir at 40°C for 2 hours, keep warm at 30°C for 2 hours, and then mix with half of the deionized water in the formula to obtain nano-ceramic emulsion.
[0047] S2. Mix the nano-ceramic emulsion with zeolite powder, calcium carbonate powder, quartz powder, BYK-024 defoamer, antibacterial wear-resistant aggregate, dispersant LD-64190, KH550 and the remaining deionized water, and stir at 300 r / min for 20 min to obtain antibacterial wear-resistant ceramic coating.
[0048] Antibacterial and wear-resistant aggregates are prepared by the following steps:
[0049] A1. Carbon fiber, sodium dodecylbenzenesulfonate, and deionized water were mixed and stirred at 40°C for 1 hour. Ammonium molybdate tetrahydrate and thiourea were added and stirred evenly. The mixture was placed in a reaction vessel and subjected to hydrothermal treatment at 220°C for 14 hours. After cooling to room temperature, the reactants were removed and washed three times with deionized water and five times with ethanol. The reactants were then dried in an oven at 60°C for 1 hour to obtain carbon fiber loaded with sheet-like nano-molybdenum disulfide. The mass ratio of carbon fiber, sodium dodecylbenzenesulfonate, deionized water, ammonium molybdate tetrahydrate, and thiourea was 1.5:0.1:80:1.5:1.
[0050] A2. Carbon fibers loaded with sheet-like molybdenum disulfide nanoparticles and gallic acid were added to deionized water and stirred at 50°C for 30 min. Zinc acetate was added and stirred evenly. Ammonia water with a concentration of 1 mol / L was added to adjust the pH to 10. The mixture was stirred at 70°C for 30 min and placed in a reaction vessel. The mixture was then subjected to hydrothermal reaction at 170°C for 2 h. After cooling to room temperature, the mixture was removed, washed three times with deionized water, and dried in a 70°C oven for 10 min to obtain modified carbon fibers. The mass ratio of carbon fibers loaded with sheet-like molybdenum disulfide nanoparticles, gallic acid, deionized water, and zinc acetate was 1.5:0.1:80:2.
[0051] A3. Mix glucose and ethanol, stir until completely dissolved, then add modified carbon fiber, stir evenly, and dry in a 70℃ oven until the ethanol evaporates. Place in a tube furnace, add a 30% potassium hydroxide solution, purge with nitrogen, and carbonize at 800℃ for 3 hours. Cool to room temperature, remove, wash three times with deionized water, and dry in a 70℃ oven for 10 minutes to obtain composite carbon fiber; the mass ratio of glucose, ethanol, modified carbon fiber, and potassium hydroxide solution is 2:40:2.5:1.
[0052] A4. Add composite carbon fiber, curcumin and tannic acid to acetone and stir evenly to obtain antibacterial and wear-resistant aggregate; the mass ratio of composite carbon fiber, curcumin, tannic acid and acetone is 2:1.2:1:50.
[0053] Example 2
[0054] An antibacterial and wear-resistant ceramic coating based on a micro-nano composite structure comprises the following raw materials in parts by weight: 70 parts silica sol, 15 parts phenyltriethoxysilane, 0.8 parts octadecyltrimethylammonium chloride, 6 parts antibacterial and wear-resistant aggregate, 3.5 parts zeolite powder, 3 parts calcium carbonate powder, 4 parts quartz powder, 0.3 parts BYK-024 defoamer, 2 parts dispersant LD-64190, 4 parts KH550, and 90 parts deionized water;
[0055] A method for preparing an antibacterial and wear-resistant ceramic coating based on a micro-nano composite structure includes the following steps:
[0056] S1. Mix silica sol, phenyltriethoxysilane and octadecyltrimethylammonium chloride, stir at 45°C for 3 hours, keep warm at 35°C for 3 hours, and then mix with half of the deionized water in the formula to obtain nano-ceramic emulsion.
[0057] S2. Mix the nano-ceramic emulsion with zeolite powder, calcium carbonate powder, quartz powder, BYK-024 defoamer, antibacterial wear-resistant aggregate, dispersant LD-64190, KH550 and the remaining deionized water, and stir at 400 r / min for 30 min to obtain antibacterial wear-resistant ceramic coating.
[0058] Antibacterial and wear-resistant aggregates are prepared by the following steps:
[0059] A1. Carbon fiber, sodium dodecylbenzenesulfonate, and deionized water were mixed and stirred at 40°C for 1 hour. Ammonium molybdate tetrahydrate and thiourea were added and stirred evenly. The mixture was placed in a reaction vessel and subjected to hydrothermal treatment at 230°C for 15 hours. After cooling to room temperature, the reactants were removed and washed three times with deionized water and five times with ethanol. The reactants were then dried in an oven at 60°C for 1 hour to obtain carbon fiber loaded with sheet-like nano-molybdenum disulfide. The mass ratio of carbon fiber, sodium dodecylbenzenesulfonate, deionized water, ammonium molybdate tetrahydrate, and thiourea was 1.8:0.2:90:1.8:1.5.
[0060] A2. Carbon fibers loaded with sheet-like molybdenum disulfide nanoparticles and gallic acid were added to deionized water and stirred at 50°C for 30 min. Zinc acetate was added and stirred until homogeneous. Ammonia solution with a concentration of 1 mol / L was added to adjust the pH to 10. The mixture was stirred at 70°C for 30 min and placed in a reaction vessel. The mixture was then subjected to hydrothermal reaction at 180°C for 3 h. After cooling to room temperature, the mixture was removed, washed three times with deionized water, and dried in a 70°C oven for 10 min to obtain modified carbon fibers. The mass ratio of carbon fibers loaded with sheet-like molybdenum disulfide nanoparticles, gallic acid, deionized water, and zinc acetate was 1.8:0.2:100:2.5.
[0061] A3. Mix glucose and ethanol, stir until completely dissolved, then add modified carbon fiber, stir evenly, and dry in a 70℃ oven until the ethanol evaporates. Place in a tube furnace, add a 30% potassium hydroxide solution, purge with nitrogen, and carbonize at 850℃ for 4 hours. Cool to room temperature, remove, wash three times with deionized water, and dry in a 70℃ oven for 10 minutes to obtain composite carbon fiber; the mass ratio of glucose, ethanol, modified carbon fiber, and potassium hydroxide solution is 2.2:45:2.8:1.3.
[0062] A4. Add composite carbon fiber, curcumin and tannic acid to acetone and stir evenly to obtain antibacterial and wear-resistant aggregate; the mass ratio of composite carbon fiber, curcumin, tannic acid and acetone is 2.5:1.2:1.3:55.
[0063] Example 3
[0064] An antibacterial and wear-resistant ceramic coating based on a micro-nano composite structure comprises the following raw materials in parts by weight: 80 parts silica sol, 20 parts phenyltriethoxysilane, 1 part octadecyltrimethylammonium chloride, 8 parts antibacterial and wear-resistant aggregate, 4 parts zeolite powder, 5 parts calcium carbonate powder, 6 parts quartz powder, 0.5 parts BYK-024 defoamer, 3 parts dispersant LD-64190, 5 parts KH550, and 100 parts deionized water;
[0065] A method for preparing an antibacterial and wear-resistant ceramic coating based on a micro-nano composite structure includes the following steps:
[0066] S1. Mix silica sol, phenyltriethoxysilane and octadecyltrimethylammonium chloride, stir at 50°C for 4 hours, keep warm at 40°C for 4 hours, and then mix with half of the deionized water in the formula to obtain nano-ceramic emulsion.
[0067] S2. Mix the nano-ceramic emulsion with zeolite powder, calcium carbonate powder, quartz powder, BYK-024 defoamer, antibacterial wear-resistant aggregate, dispersant LD-64190, KH550 and the remaining deionized water, and stir at 500 r / min for 40 min to obtain antibacterial wear-resistant ceramic coating.
[0068] Antibacterial and wear-resistant aggregates are prepared by the following steps:
[0069] A1. Carbon fiber, sodium dodecylbenzenesulfonate, and deionized water were mixed and stirred at 40°C for 1 hour. Ammonium molybdate tetrahydrate and thiourea were added and stirred evenly. The mixture was placed in a reaction vessel and subjected to hydrothermal treatment at 250°C for 16 hours. After cooling to room temperature, the reactants were removed and washed three times with deionized water and five times with ethanol. The reactants were then dried in an oven at 60°C for 1 hour to obtain carbon fiber loaded with sheet-like nano-molybdenum disulfide. The mass ratio of carbon fiber, sodium dodecylbenzenesulfonate, deionized water, ammonium molybdate tetrahydrate, and thiourea was 2:0.3:100:2:2.
[0070] A2. Carbon fibers loaded with sheet-like molybdenum disulfide nanoparticles and gallic acid were added to deionized water and stirred at 50°C for 30 min. Zinc acetate was added and stirred evenly. Ammonia water with a concentration of 1 mol / L was added to adjust the pH to 10. The mixture was stirred at 70°C for 30 min and placed in a reaction vessel. The mixture was then subjected to hydrothermal reaction at 190°C for 4 h. After cooling to room temperature, the mixture was removed, washed three times with deionized water, and dried in a 70°C oven for 10 min to obtain modified carbon fibers. The mass ratio of carbon fibers loaded with sheet-like molybdenum disulfide nanoparticles, gallic acid, deionized water, and zinc acetate was 2:0.3:120:3.
[0071] A3. Mix glucose and ethanol, stir until completely dissolved, then add modified carbon fiber, stir evenly, and dry in a 70℃ oven until the ethanol evaporates. Place in a tube furnace, add a 30% potassium hydroxide solution, purge with nitrogen, and carbonize at 900℃ for 5 hours. Cool to room temperature, remove, wash three times with deionized water, and dry in a 70℃ oven for 10 minutes to obtain composite carbon fiber; the mass ratio of glucose, ethanol, modified carbon fiber, and potassium hydroxide solution is 2.3:50:3:1.5.
[0072] A4. Add composite carbon fiber, curcumin and tannic acid to acetone and stir evenly to obtain antibacterial and wear-resistant aggregate; the mass ratio of composite carbon fiber, curcumin, tannic acid and acetone is 3:1.5:1.5:60.
[0073] Comparative Example 1
[0074] The only difference between this comparative example and Example 3 is the preparation of the antibacterial and wear-resistant aggregate, as detailed below:
[0075] Antibacterial and wear-resistant aggregates are prepared by the following steps:
[0076] A1. Add carbon fiber and gallic acid to deionized water, stir at 50℃ for 30 min, add zinc acetate, stir evenly, add 1 mol / L ammonia water to adjust pH to 10, stir at 70℃ for 30 min, place in a reaction vessel, hydrothermally react at 190℃ for 4 h, cool to room temperature, remove, wash 3 times with deionized water, dry in a 70℃ oven for 10 min to obtain modified carbon fiber; the mass ratio of loaded carbon fiber, gallic acid, deionized water and zinc acetate is 2:0.3:120:3;
[0077] A2. Mix glucose and ethanol, stir until completely dissolved, then add modified carbon fiber, stir evenly, and dry in a 70℃ oven until the ethanol evaporates. Place in a tube furnace, add a 30% potassium hydroxide solution, purge with nitrogen, and carbonize at 900℃ for 5 hours. Cool to room temperature, remove, wash three times with deionized water, and dry in a 70℃ oven for 10 minutes to obtain composite carbon fiber; the mass ratio of glucose, ethanol, modified carbon fiber, and potassium hydroxide solution is 2.3:50:3:1.5.
[0078] A3. Add composite carbon fiber, curcumin and tannic acid to acetone and stir evenly to obtain antibacterial and wear-resistant aggregate; the mass ratio of composite carbon fiber, curcumin, tannic acid and acetone is 3:1.5:1.5:60.
[0079] Comparative Example 2
[0080] The only difference between this comparative example and Example 3 is the preparation of the antibacterial and wear-resistant aggregate, as detailed below:
[0081] Antibacterial and wear-resistant aggregates are prepared by the following steps:
[0082] A1. Carbon fiber, sodium dodecylbenzenesulfonate, and deionized water were mixed and stirred at 40°C for 1 hour. Ammonium molybdate tetrahydrate and thiourea were added and stirred evenly. The mixture was placed in a reaction vessel and subjected to hydrothermal treatment at 250°C for 16 hours. After cooling to room temperature, the reactants were removed and washed three times with deionized water and five times with ethanol. The reactants were then dried in an oven at 60°C for 1 hour to obtain carbon fiber loaded with sheet-like nano-molybdenum disulfide. The mass ratio of carbon fiber, sodium dodecylbenzenesulfonate, deionized water, ammonium molybdate tetrahydrate, and thiourea was 2:0.3:100:2:2.
[0083] A2. Mix glucose and ethanol, stir until completely dissolved, then add carbon fibers loaded with sheet-like molybdenum disulfide nanoparticles, stir evenly, and dry in a 70℃ oven until the ethanol evaporates. Place in a tube furnace, add a 30% potassium hydroxide solution, purge with nitrogen, and carbonize at 900℃ for 5 hours. Cool to room temperature, remove, wash three times with deionized water, and dry in a 70℃ oven for 10 minutes to obtain composite carbon fibers. The mass ratio of glucose, ethanol, carbon fibers loaded with sheet-like molybdenum disulfide nanoparticles, and potassium hydroxide solution is 2.3:50:3:1.5.
[0084] A3. Add composite carbon fiber, curcumin and tannic acid to acetone and stir evenly to obtain antibacterial and wear-resistant aggregate; the mass ratio of composite carbon fiber, curcumin, tannic acid and acetone is 3:1.5:1.5:60.
[0085] Comparative Example 3
[0086] The only difference between this comparative example and Example 3 is the preparation of the antibacterial and wear-resistant aggregate, as detailed below:
[0087] Antibacterial and wear-resistant aggregates are prepared by the following steps:
[0088] A1. Carbon fiber, sodium dodecylbenzenesulfonate, and deionized water were mixed and stirred at 40°C for 1 hour. Ammonium molybdate tetrahydrate and thiourea were added and stirred evenly. The mixture was placed in a reaction vessel and subjected to hydrothermal treatment at 250°C for 16 hours. After cooling to room temperature, the reactants were removed and washed three times with deionized water and five times with ethanol. The reactants were then dried in an oven at 60°C for 1 hour to obtain carbon fiber loaded with sheet-like nano-molybdenum disulfide. The mass ratio of carbon fiber, sodium dodecylbenzenesulfonate, deionized water, ammonium molybdate tetrahydrate, and thiourea was 2:0.3:100:2:2.
[0089] A2. Carbon fibers loaded with sheet-like molybdenum disulfide nanoparticles and gallic acid were added to deionized water and stirred at 50°C for 30 min. Zinc acetate was added and stirred evenly. Ammonia water with a concentration of 1 mol / L was added to adjust the pH to 10. The mixture was stirred at 70°C for 30 min and placed in a reaction vessel. The mixture was then subjected to hydrothermal reaction at 190°C for 4 h. After cooling to room temperature, the mixture was removed, washed three times with deionized water, and dried in a 70°C oven for 10 min to obtain modified carbon fibers. The mass ratio of carbon fibers loaded with sheet-like molybdenum disulfide nanoparticles, gallic acid, deionized water, and zinc acetate was 2:0.3:120:3.
[0090] A3. Add modified carbon fiber, curcumin and tannic acid to acetone and stir evenly to obtain antibacterial and wear-resistant aggregate; the mass ratio of modified carbon fiber, curcumin, tannic acid and acetone is 3:1.5:1.5:60.
[0091] Comparative Example 4
[0092] The only difference between this comparative example and Example 3 is the preparation of the antibacterial and wear-resistant aggregate, as detailed below:
[0093] Antibacterial and wear-resistant aggregates are prepared by the following steps:
[0094] A1. Carbon fiber, sodium dodecylbenzenesulfonate, and deionized water were mixed and stirred at 40°C for 1 hour. Ammonium molybdate tetrahydrate and thiourea were added and stirred evenly. The mixture was placed in a reaction vessel and subjected to hydrothermal treatment at 250°C for 16 hours. After cooling to room temperature, the reactants were removed and washed three times with deionized water and five times with ethanol. The reactants were then dried in an oven at 60°C for 1 hour to obtain carbon fiber loaded with sheet-like nano-molybdenum disulfide. The mass ratio of carbon fiber, sodium dodecylbenzenesulfonate, deionized water, ammonium molybdate tetrahydrate, and thiourea was 2:0.3:100:2:2.
[0095] A2. Carbon fibers loaded with sheet-like molybdenum disulfide nanoparticles and gallic acid were added to deionized water and stirred at 50°C for 30 min. Zinc acetate was added and stirred evenly. Ammonia water with a concentration of 1 mol / L was added to adjust the pH to 10. The mixture was stirred at 70°C for 30 min and placed in a reaction vessel. The mixture was then subjected to hydrothermal reaction at 190°C for 4 h. After cooling to room temperature, the mixture was removed, washed three times with deionized water, and dried in a 70°C oven for 10 min to obtain modified carbon fibers. The mass ratio of carbon fibers loaded with sheet-like molybdenum disulfide nanoparticles, gallic acid, deionized water, and zinc acetate was 2:0.3:120:3.
[0096] A3. Mix glucose and ethanol, stir until completely dissolved, then add modified carbon fiber, stir evenly, and dry in a 70℃ oven until the ethanol evaporates. Place in a tube furnace, add a 30% potassium hydroxide solution, purge with nitrogen, and carbonize at 900℃ for 5 hours. Cool to room temperature, remove, wash three times with deionized water, and dry in a 70℃ oven for 10 minutes to obtain composite carbon fiber; the mass ratio of glucose, ethanol, modified carbon fiber, and potassium hydroxide solution is 2.3:50:3:1.5.
[0097] A4. Add composite carbon fiber and tannic acid to acetone and stir evenly to obtain antibacterial and wear-resistant aggregate; the mass ratio of composite carbon fiber, tannic acid and acetone is 3:3:60.
[0098] Comparative Example 5
[0099] The only difference between this comparative example and Example 3 is the preparation of the antibacterial wear-resistant aggregate, as detailed below: The antibacterial wear-resistant aggregate is prepared by the following steps:
[0100] A1. Carbon fiber, sodium dodecylbenzenesulfonate, and deionized water were mixed and stirred at 40°C for 1 hour. Ammonium molybdate tetrahydrate and thiourea were added and stirred evenly. The mixture was placed in a reaction vessel and subjected to hydrothermal treatment at 250°C for 16 hours. After cooling to room temperature, the reactants were removed and washed three times with deionized water and five times with ethanol. The reactants were then dried in an oven at 60°C for 1 hour to obtain carbon fiber loaded with sheet-like nano-molybdenum disulfide. The mass ratio of carbon fiber, sodium dodecylbenzenesulfonate, deionized water, ammonium molybdate tetrahydrate, and thiourea was 2:0.3:100:2:2.
[0101] A2. Carbon fibers loaded with sheet-like molybdenum disulfide nanoparticles and gallic acid were added to deionized water and stirred at 50°C for 30 min. Zinc acetate was added and stirred evenly. Ammonia water with a concentration of 1 mol / L was added to adjust the pH to 10. The mixture was stirred at 70°C for 30 min and placed in a reaction vessel. The mixture was then subjected to hydrothermal reaction at 190°C for 4 h. After cooling to room temperature, the mixture was removed, washed three times with deionized water, and dried in a 70°C oven for 10 min to obtain modified carbon fibers. The mass ratio of carbon fibers loaded with sheet-like molybdenum disulfide nanoparticles, gallic acid, deionized water, and zinc acetate was 2:0.3:120:3.
[0102] A3. Mix glucose and ethanol, stir until completely dissolved, then add modified carbon fiber, stir evenly, and dry in a 70℃ oven until the ethanol evaporates. Place in a tube furnace, add a 30% potassium hydroxide solution, purge with nitrogen, and carbonize at 900℃ for 5 hours. Cool to room temperature, remove, wash three times with deionized water, and dry in a 70℃ oven for 10 minutes to obtain composite carbon fiber; the mass ratio of glucose, ethanol, modified carbon fiber, and potassium hydroxide solution is 2.3:50:3:1.5.
[0103] A4. Add composite carbon fiber and curcumin to acetone and stir evenly to obtain antibacterial and wear-resistant aggregate; the mass ratio of composite carbon fiber, curcumin and acetone is 3:3:60.
[0104] The antibacterial and wear-resistant ceramic coatings prepared in Examples 1-3 and Comparative Examples 1-5 were then subjected to performance tests. The specific test methods are as follows:
[0105] Antibacterial performance test: The antibacterial and wear-resistant ceramic coating prepared was tested according to GB / T21866-2008 standard.
[0106] Abrasion resistance test: The abrasion resistance effect of the prepared antibacterial abrasion-resistant ceramic coating was tested using an abrasion testing machine, referring to the method described in GB / T1768-2006.
[0107] The specific test results are shown in Table 1.
[0108] Table 1 Performance testing of antibacterial and wear-resistant ceramic coatings prepared in Examples 1-3 and Comparative Examples 1-5
[0109]
[0110] As shown in Table 1, the antibacterial and wear-resistant ceramic coatings of all embodiments outperform the reference product, and the prepared antibacterial and wear-resistant ceramic coatings exhibit high wear resistance and antibacterial properties. This fully demonstrates the effectiveness of the antibacterial and wear-resistant ceramic coatings provided by this invention.
[0111] Comparative Example 1 replaced the carbon fibers loaded with flake-shaped nano-molybdenum disulfide with antibacterial and wear-resistant aggregates prepared from carbon fibers and added them to the coating. The wear resistance and antibacterial properties decreased, which proved that the flake-shaped nano-molybdenum disulfide synthesized on the carbon fiber surface has high wear resistance, can consume the energy generated by friction, and improve the wear resistance of ceramic coatings. In addition, the nano-zinc oxide filled between the flake-shaped nano-molybdenum disulfide is protected by the flake-shaped nano-molybdenum disulfide, preventing the nano-zinc oxide from easily migrating and precipitating out during frequent cleaning and scratching, thus affecting the antibacterial activity of the ceramic coating.
[0112] Comparative Example 2 showed that when the modified carbon fiber was replaced with carbon fiber loaded with sheet-like nano-molybdenum disulfide, the antibacterial and wear-resistant aggregate prepared was added to the coating. The wear resistance and antibacterial properties decreased, which proved that the synthesized nano-zinc oxide, as an inorganic antibacterial agent, can improve the antibacterial activity of ceramic coatings. Moreover, the uneven antibacterial layer formed on the surface of sheet-like nano-molybdenum disulfide or carbon fiber can form an antibacterial and wear-resistant layer in the ceramic coating, thereby enhancing the antibacterial and wear-resistant properties of the ceramic coating.
[0113] Comparative Example 3 showed that when the composite carbon fiber was replaced with the antibacterial and wear-resistant aggregate prepared by modified carbon fiber, the wear resistance and antibacterial properties of the coating decreased. This demonstrates that the porous carbon layer formed on the surface of the modified carbon fiber has high adsorption performance, which can adsorb and fix the nano zinc oxide particles on the surface of the modified carbon fiber. This prevents the nano zinc oxide from easily migrating and precipitating out during frequent cleaning and scratching of the ceramic coating, thus affecting the antibacterial activity of the ceramic coating. Furthermore, when the ceramic coating comes into contact with bacteria, the adsorption performance of the porous carbon layer allows the bacteria to enter the pores, increasing the penetration time of the bacteria. The bacteria inhaled into the pores are eliminated under the action of nano zinc oxide, thereby achieving the purpose of the porous carbon layer hindering the bacteria and the nano zinc oxide sterilizing them.
[0114] Comparative Example 4, where curcumin was replaced by tannic acid at the same mass, and Comparative Example 5, where tannic acid was replaced by curcumin at the same mass, prepared antibacterial and wear-resistant aggregates, were added to the coating. The wear resistance and antibacterial properties decreased, proving that curcumin and tannic acid form an organic antibacterial layer on the surface of composite carbon fibers. When added to ceramic coatings, they form an organic-inorganic antibacterial system, enhancing the antibacterial properties of the ceramic coatings. Furthermore, curcumin and tannic acid provide a large number of oxygen-containing functional groups on the surface of composite carbon fibers, improving the dispersibility of composite carbon fibers in ceramic coatings and enhancing the antibacterial and wear-resistant properties of ceramic coatings.
[0115] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0116] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
[0117] Those skilled in the art should understand that the above descriptions are merely several specific embodiments of the present invention, and not all embodiments.
Claims
1. An antibacterial and wear-resistant ceramic coating based on a micro-nano composite structure, characterized in that, The raw materials include the following parts by weight: 60-80 parts silica sol, 10-20 parts phenyltriethoxysilane, 0.5-1 part surfactant, 5-8 parts antibacterial and wear-resistant aggregate, 3-4 parts zeolite powder, 2-5 parts calcium carbonate powder, 3-6 parts quartz powder, 0.1-0.5 parts defoamer, 1-3 parts dispersant, 3-5 parts coupling agent, and 80-100 parts deionized water; The antibacterial and wear-resistant aggregate is obtained by reacting modified carbon fiber and glucose together, and then reacting them with curcumin and tannic acid. The modified carbon fiber is obtained by synthesizing sheet-like nano-molybdenum disulfide on the surface of carbon fiber, and then reacting it with zinc acetate and ammonia. The antibacterial and wear-resistant aggregate is prepared by the following steps: A1. Mix carbon fiber, sodium dodecylbenzenesulfonate and deionized water, stir, add ammonium molybdate tetrahydrate and thiourea, stir, place in a reaction vessel, hydrothermally treat at 220-250℃ for 14-16h, cool to room temperature, take out the reactant, wash the reactant, dry, and obtain carbon fiber loaded with sheet-like nano molybdenum disulfide. A2. Add carbon fibers loaded with sheet-like nano molybdenum disulfide and gallic acid to deionized water, stir, add zinc acetate, stir evenly, add ammonia to adjust pH, stir, place in a reaction vessel, and hydrothermally react at 170-190℃ for 2-4 hours. Cool to room temperature, take out, wash, and dry to obtain modified carbon fibers. A3. Mix glucose and ethanol, stir until completely dissolved, add modified carbon fiber, stir evenly, dry until ethanol evaporates, place in a tube furnace, add potassium hydroxide solution, purge with nitrogen, carbonize at 800-900℃ for 3-5 hours, cool to room temperature, remove, wash, and dry to obtain composite carbon fiber. A4. Add composite carbon fiber, curcumin and tannic acid to acetone and stir evenly to obtain antibacterial and wear-resistant aggregate.
2. The antibacterial and wear-resistant ceramic coating based on a micro-nano composite structure according to claim 1, characterized in that, In step A1, the mass ratio of the carbon fiber, sodium dodecylbenzenesulfonate, deionized water, ammonium molybdate tetrahydrate and thiourea is (1.5-2):(0.1-0.3):(80-100):(1.5-2):(1-2).
3. The antibacterial and wear-resistant ceramic coating based on a micro-nano composite structure according to claim 1, characterized in that, In step A2, the mass ratio of the carbon fiber loaded with sheet-like molybdenum disulfide nanoparticles, gallic acid, deionized water and zinc acetate is (1.5-2):(0.1-0.3):(80-120):(2-3).
4. The antibacterial and wear-resistant ceramic coating based on a micro-nano composite structure according to claim 1, characterized in that, In step A3, the mass ratio of glucose, ethanol, modified carbon fiber and potassium hydroxide solution is (2-2.3):(40-50):(2.5-3):(1-1.5).
5. The antibacterial and wear-resistant ceramic coating based on a micro-nano composite structure according to claim 1, characterized in that, In step A4, the mass ratio of the composite carbon fiber, curcumin, tannic acid, and acetone is (2-3):(1.2-1.5):(1-1.5):(50-60).
6. The antibacterial and wear-resistant ceramic coating based on a micro-nano composite structure according to claim 1, characterized in that, The surfactant is octadecyltrimethylammonium chloride; the coupling agent is KH550.
7. The antibacterial and wear-resistant ceramic coating based on a micro-nano composite structure according to claim 1, characterized in that, The dispersant is selected from dispersant LD-64190 and dispersant LD-6408.
8. The antibacterial and wear-resistant ceramic coating based on a micro-nano composite structure according to claim 1, characterized in that, The defoamer is selected from BYK-024 defoamer and BYK-055 defoamer.
9. The antibacterial and wear-resistant ceramic coating based on a micro-nano composite structure according to claim 1, characterized in that, The preparation method of the antibacterial and wear-resistant ceramic coating includes the following steps: S1. Mix silica sol, phenyltriethoxysilane and surfactant, stir at 40-50℃ for 2-4 hours, keep warm at 30-40℃ for 2-4 hours, and then mix with half of the deionized water in the formula to obtain nano-ceramic emulsion. S2. Mix the nano-ceramic emulsion with zeolite powder, calcium carbonate powder, quartz powder, defoamer, antibacterial wear-resistant aggregate, dispersant, coupling agent and remaining deionized water, and stir at 300-500 r / min for 20-40 min to obtain antibacterial wear-resistant ceramic coating.
Citation Information
Patent Citations
Aqueous wear-resistant super-hydrophobic and super-oleophobic nano composite coating and preparation method thereof
CN111019447A
Preparation method and application of composite material with 1T-phase MoS2-coated rGO growing on carbon fibers
CN113981673A